Animal health and food safety in smallholder pig value chains in Vietnam - Unger, Fred; Lapar, Ma. Lucila; Pham Van Hung; Sinh Dang Xuan; Pham Hong Ngan; Duong Van Nhiem; Hung Nguyen-Viet; Grace, Delia (International Livestock Research Institute, 2015)
Pork represents more than 70% of meat consumption in Vietnam and production delivers significant benefits to smallholders who supply 80% of the market. Lack of technologies and poor hygienic/biosecurity measures are common challenges resulting in increased disease risk (including food borne) along the chain. Vietnamese consumers prefer fresh, un-chilled pork provided at outlets supplied by smallholders but increasingly concerns about pig diseases and food safety are expressed by consumers. While research has been done at selected nodes of the chain (e.g. slaughterhouses), “farm to fork” approaches are still lacking. Here we present selected results and the development of feasible interventions from an ongoing study involving two provinces of Vietnam (Nghe An and Hung Yen) that aims for improved productivity and food safety in smallholder pig value chains. An initial assessment phase (finalized) is followed by interventions targeting identification of “best bets” (ongoing). Involved chain actors range from suppliers, via producers, slaughterhouses/markets to consumers. Data collection comprises quantitative and qualitative tools supported by a microbiological risk assessment. Identified constraints along key nodes of the chain include, for example, poor on-farm and slaughterhouse hygiene determined by presence of biological hazards aligned with rudimentary control/prevention measures. Selected results on food safety include considerable high pathogen loads for Salmonella along the chain (e.g. on-farm drinking water, 19%; slaughterhouses, floor swabs 22%; and, pork cuts at markets, 45%). Basic on-farm biosecurity is rare (e.g. use of disinfection matrices, quarantine or visitor control). Examples for the development of specific interventions will be discussed.